Odpowiedzi

2010-03-23T20:29:09+01:00
A 2(x+3)=10
2x+6=10
2x=4
x=2
b 3(x-1) + 2+=8
3x-3+2=8
3x=9
x=3
c 2(13-x)-9=1
26-2x-9=1
-2x+17=1
-2x=-16
2x=16
x=8
d 3( 1 - x)+2=-7
3-3x+2=-7
-3x+5=-7
-3x=-12
3x=12
x=4
e 3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x-x=9-9
0≠0
f 4( 3x+2)+5(2x+3)=-(2x+13)
12x+8+10x+15=-2x-13
22x+23=-2x-13
20x=-36
x=-1,8
g 4(x-2)-2(x-4=5(x+1)-3x
4x-8-2x+8=5x+5-3x
2x=2x+5
0≠5
h 2 (x-4)=2(2x-1)+6(x+1)
2x-8=4x-2+6x+6
2x=10x+4+8
2x-10x=12
-8x=12
8x=-12
x=-1,5
2010-03-23T20:31:31+01:00
A
2(x+3)=10
2x+6=10
2x=10-6
2x=4
x=2

b
3(x-1) + 2+=8
3x-3+2=8
3x=8+3-2
3x=9
x=3

c
2(13-x)-9=1
26-2x-9=1
-2x=1-26+9
-2x=-16
x=8

d
3( 1 - x)+2=-7
3-3x+2=-7
-3x=-7-3-2
-3x=-12
x=4

e
3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x-x=8+1-9
0=0

f
4( 3x+2)+5(2x+3)=-(2x+13)
12x+8+10x+15=-2x-13
12x+10x+2x=-13-8-15
24x=-36
x=-1,5

g
4(x-2)-2(x-4=5(x+1)-3x
4x-8-2x+8=5x+5-3x
4x-2x-5x+3x=5+8-8
0≠5

h
2 (x-4)=2(2x-1)+6(x+1)
2x-8=4x-2+6x+6
2x-4x-6x=-2+6+8
-8x=12
x=-1,5
2010-03-23T20:33:54+01:00
A) 2(x+3)=10
2x + 6 = 10 / -6
2x = 4 / :2
x = 2

b) 3(x-1) + 2=8
3x - 3 + 2 = 8
3x - 1 = 8 / +1
3x = 9 / :3
x = 3

c) 2(13-x)-9=1
26 - 2x - 9 = 1
17 - 2x = 1 / -17
-2x = -16 / :(-2)
x = 8

d) 3( 1 - x)+2=-7
3 - 3x + 2 = -7
5 - 3x = -7 / -5
-3x = -12 / :(-3)
x = 4

e) 3(x+3)=2(x+4)+x+1
3x + 9 = 2x + 8 + x + 1
3x + 9 = 3x + 9 / -9
3x = 3x / -3x
0=0

f) 4( 3x+2)+5(2x+3)=-(2x+13)
12x + 8 + 10x + 15 = -2x -13
22x + 23 = -2x -13 / +2x
24x + 23 = -13 / -23
24x = -36 / :24
x = -1,5

g) 4(x-2)-2(x-4)=5(x+1)-3x
4x - 8 - 2x + 8 = 5x + 5 - 3x
2x = 2x + 5 / -2x
0 = 5 (r.sprzeczne)

h) 2(x-4)=2(2x-1)+6(x+1)
2x - 8 = 4x - 2 + 6x + 6
2x - 8 = 10x + 4 / +8
2x = 10x + 12 / -10x
-8x = 12 / :(-8)
x = -1,5